Whole-genome sequencing and comparative genomics reveal antimicrobial potential and adaptive traits of Bacillus velezensis AM12 - Qianqian Lin; Fengzhi Pan; JinJin Yang; Ruixue pan; Haotian Ma; Shiyun Wu; Mingyuan Jia; Huayuan Xu; Jingchun Wu; Jinju Peng; Yuexia Ding; Fucheng Guo; et al. (Functional & Integrative Genomics, 2026)

Climate–morphology dual regulation of urban land surface temperature: A multi-scale decomposition of driving mechanisms within a baseline–restructuring–fine-tuning framework - Wenguang Xiang; Shuangyun Peng; Fucheng Cai; Juexian Dong; Zhiqiang Lin; Xingqiang Feng; Xianchun Pan; Weihang Wang; Biting Cui; Fapeng Cai (Sustainable Cities and Society, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Corrigendum to “Spring phenology in subtropical trees: Developing process-based models on an experimental basis” [Agricultural and Forest Meteorology 314 (2022) 108802] - Rui Zhang; Jianhong Lin; Fucheng Wang; Nicolas Delpierre; Koen Kramer; Heikki Hänninen; Jiasheng Wu (Agricultural and Forest Meteorology, 2026)

CPK12 decodes effector-triggered calcium signaling and phosphorylates PIP2;1 to facilitate apoplastic ROS transport into the cytoplasm in Arabidopsis - Zhiyi Jia; Weiwei Yu; Xijie Guo; Jianwei Li; Fan Qi; Yayun Zhu; Xinzhong Cai; Xiaoting Li; Ning Li; Hansong Dong; Fucheng Lin; Yan Liang (Molecular Plant, 2025)

Salvia japonica essential oil as biocontrol agent: suppressing Fusarium oxysporum in Pinus sylversteis Var. Mongolica seedling blight - Jingyu Ji; Qiuer Sa; Cheng Chen; Yundi Zhang; Fucheng Lin; Wenzhuo Sun; Jie Zhang; Guocai Zhang; Weihu Ma (Australasian Plant Pathology, 2025)

Confined ionic association and its effect on Li+/Mg2+ permselective transport through the HKUST-1 nanopore - Jianduo Zhang; Fucheng Dai; Jianbo Li; Dawei He; Xuan Lin; Xiaobin Jiang; Junjiang Bao; Xiaopeng Zhang; Gaohong He; Ning Zhang (Desalination, 2025)

Amplification-free and label-free rapid detection of Staphylococcus aureus using solution-gated graphene transistor-based DNA biosensor with hybridization enhancement by interface engineering - Jiayuan Zheng; Jinhua Li; Tianci Lin; Zhanpeng Ren; Fucheng Wang; Zhonghao Shi; Haiyang Yu; Wei Jiang; Wei Tang (Chemical Engineering Journal, 2024)

The paleo-lithospheric structure and rifting-magmatic processes of the northern South China Sea passive margin - Zhongxian Zhao; Zhen Sun; Ning Qiu; Minghui Zhao; Jiazheng Zhang; Fucheng Li; Jian Lin; Eun Young Lee (Gondwana Research, 2023)

Evaluation of cold plasma for decontamination of molds and mycotoxins in rice grain - Jian Guo; Zhiping He; Chao Ma; Wanting Li; Jiaoyu Wang; Fucheng Lin; Xingquan Liu; Ling Li (Food Chemistry, 2023)

High autumn temperatures increase the depth of bud dormancy in the subtropical Torreya grandis and Carya illinoinensis and delay leaf senescence in the deciduous Carya - Fucheng Wang; Rui Zhang; Jianhong Lin; Jinbin Zheng; Heikki Hänninen; Jiasheng Wu (Trees, 2022)

The basic helix–loop–helix transcription factor Crf1 is required for development and pathogenicity of the rice blast fungus by regulating carbohydrate and lipid metabolism - Huijuan Cao; Pengyun Huang; Yuxin Yan; Yongkai Shi; Bo Dong; Xiaohong Liu; Lidan Ye; Fucheng Lin; Jianping Lu (Environmental Microbiology, 2018)
Summary Pyricularia oryzae is a plant pathogen causing rice blast, a serious disease spreading in cultivated rice globally. Transcription factors play important regulatory roles in fungal development and pathogenicity. Here, we characterized the biological functions of Crf1, a basic helix–loop–helix (bHLH) transcription factor, in the development and pathogenicity of P. oryzae with functional genetics, molecular and biochemical approaches. We found that CRF1 is necessary for virulence and plays an indispensable role in the regulation of carbohydrate and lipid metabolism in P. oryzae . Deletion of CRF1 led to defects in utilization of lipids, ethanol, glycerol and L‐arabinose, and down‐regulation of many important genes in lipolysis, β ‐oxidation, gluconeogenesis, as well as glycerol and arabinose metabolism. CRF1 is also essential for peroxisome and vacuole function, and conidial cell death during appressorium formation. The appressorium turgor, penetration ability and virulence in Δ crf1 were restored by supplementation of exogenous glucose. The virulence of Crf1 mutant was also recovered by adding exogenous D‐xylose, but not by addition of ethanol, pyruvate, leucine or L‐arabinose. These data showed that Crf1 plays an important role in the complex regulatory network of carbohydrate and lipid metabolism that governs fungal development and pathogenicity.

Three duplication events and variable molecular evolution characteristics involved in multiple GGPS genes of six Solanaceae species - FENG LI; CHUNYANG WEI; CHAN QIAO; ZHENXI CHEN; PENG WANG; PAN WEI; RAN WANG; LIFENG JIN; JUN YANG; FUCHENG LIN; ZHAOPENG LUO (Journal of Genetics, 2016)

Downregulation of the lycopene ε-cyclase gene confers tolerance to salt and drought stress in Nicotiana tabacum - Yanmei Shi; Pingping Liu; Yuzhen Xia; Pan Wei; Wenzheng Li; Wei Zhang; Xia Chen; Peijian Cao; Yalong Xu; Lifeng Jin; Feng Li; Zhaopeng Luo; et al. (Acta Physiologiae Plantarum, 2015)

Analysis of the sucrose synthase gene family in tobacco: structure, phylogeny, and expression patterns - Zhong Wang; Pan Wei; Mingzhu Wu; Yalong Xu; Feng Li; Zhaopeng Luo; Jianfeng Zhang; Ang Chen; Xiaodong Xie; Peijian Cao; Fucheng Lin; Jun Yang (Planta, 2015)

An ATP-dependent protease homolog ensures basic standards of survival and pathogenicity for Magnaporthe oryzae - Jian Li; Xilong Liang; Yi Wei; Jinliang Liu; Fucheng Lin; Shi-Hong Zhang (European Journal of Plant Pathology, 2015)

Endophytic Diaporthe from Southeast China are genetically diverse based on multi-locus phylogeny analyses - Jiaying Wang; Xihui Xu; Lijuan Mao; Jiaping Lao; Fucheng Lin; Zhilin Yuan; Chulong Zhang (World Journal of Microbiology and Biotechnology, 2014)